Aggression as a Predictor of Early Substance Use Initiation Among Youth With Family Histories of Substance Use Disorders. (December 2015) - Mathias, Charles W.; Duffing, Tiffany M.; Acheson, Ashley; Charles, Nora E.; Lake, Sarah L.; Ryan, Stacy R.; Liang, Yuanyuan; Dougherty, Donald M.
Abstract : Objectives: Risk for substance use disorders is widely studied, but relatively less is known about risk of early substance use initiation. Childhood aggression has been identified as predictive of early substance use initiation, although it typically is measured as a heterogenous mix of behaviors that may underestimate the magnitude of this relationship. The purpose of this study was to extend prior research by investigating the relationship of distinct aggressive behaviors with early substance use initiation among youths with family histories of substance use disorders. Methods: Children (ages 10 to 12 years) with a family history of substance use disorder were tested on a variety of potential risk factors and monitored for substance use initiation prospectively at 6-month intervals. By age 14, 41 youth initiated substance use and 78 had not. Comparisons were made examining predictive relationships between specific aggressive behaviors, externalizing symptoms, internalizing symptoms, and social adjustment with early initiation of substance use (extending the approach of Ernst and colleagues). Results: Children who had assaulted people and had school discipline problems due to aggressive behavior were at increased odds of early substance use initiation. Even in the context of family history of substance use disorder, individual differences in childhood aggression confer increased risk for early substance use initiation. Discussion: Even in the context of family history of substance use disorder, individual differences in childhood aggression and thought problems confer increased risk for early substance use initiation.